Numerical Simulation on the Seepage Properties of Soil-Rock Mixture - Ning Zhao; Yingchao Wang; Bo Meng; Ning Luo (Advances in Materials Science and Engineering)
To reveal the mechanism of water inrush in a fault tunnel and study the influence of different structures on the seepage process, a filling structure composed of a soil skeleton (fixed particles), a movable particles phase, and a water phase is constructed to simulate the rock mass broken by the fault. Fluent software is used to simulate the migration of the water phase in three different filling structures under different initial water velocities and dynamic viscosities. The variation law of the seepage time with the initial water velocity and dynamic viscosity in the three types of filling structures is obtained. The research shows the following: (1) the looser the filling structure, the greater the influence of gravity on the water phase seepage; the more compact the filling structure, the greater the spread range of the water phase and the more uniform the spread of the water phase. (2) The seepage time decreases with the increase in the initial water velocity. The seepage time and initial water velocity can be fitted by an exponential function. The effect of initial water velocity on seepage time is much greater than that of the structure. (3) The seepage time is related to both the dynamic viscosity and the structure. The seepage time increases with the increase in dynamic viscosity.